2017
DOI: 10.1042/bcj20160760
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between intersubunit transmembrane domains regulate the chaperone-dependent degradation of an oligomeric membrane protein

Abstract: In the kidney, the epithelial sodium channel (ENaC) regulates blood pressure through control of sodium and volume homeostasis, and in the lung, ENaC regulates the volume of airway and alveolar fluids. ENaC is a heterotrimer of homologous α-, β- and γ-subunits, and assembles in the endoplasmic reticulum (ER) before it traffics to and functions at the plasma membrane. Improperly folded or orphaned ENaC subunits are subject to ER quality control and targeted for ER-associated degradation (ERAD). We previously est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 98 publications
5
22
0
Order By: Relevance
“…After immunoprecipitation, we observed that the 125 I-ubiquitin signal was equal to or greater than the predicted molecular weight for Chimera A* on the autoradiograph (Figure 6B, arrow), as observed previously for Ste6p* and other substrates (Nakatsukasa et al. , 2008; Buck et al. , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…After immunoprecipitation, we observed that the 125 I-ubiquitin signal was equal to or greater than the predicted molecular weight for Chimera A* on the autoradiograph (Figure 6B, arrow), as observed previously for Ste6p* and other substrates (Nakatsukasa et al. , 2008; Buck et al. , 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Subunit-specific interactions have also been shown with ENaC and Lhs1/GRP170, an ER-resident Hsp70-like chaperone protein (33). Lhs1/GRP170 -mediated ENaC degradation was specific for the ␣ subunit expressed alone and was blocked when the other two subunits were present in the channel complex (33,56). Nonetheless, our data show that PON-2 interacts with ENaC subunits in a heterologous expression system and raise the possibility that these interactions occur in the distal nephron and perhaps in other epithelia.…”
Section: Pon-2 Inhibits Enacmentioning
confidence: 95%
“…Carbonate extraction was conducted on yeast expressing ApoB essentially as described . This procedure has long been used as a means to remove peripherally associated proteins bound to membranes .…”
Section: Methodsmentioning
confidence: 99%